Effectiveness of Acceptance and Commitment Therapy and Structured Exercise Program on Defense Mechanism and Eating Behavior in Relation to Body Mass Index among University Students - Patricia Pawa, Pitil (Global Business & Management Research: An International Journal, 2021)
Obesity is a significant public health issue among Malaysians and is rising among university students. Following the COVID-19 pandemic and the restrictions imposed by the government through the Movement Control Order (MCO), the prevalence rate of being overweight or obese has been increasing. The lack of physical activity and unhealthy eating behaviors have influenced the body weight of university students. Individuals who are obese may experience weight-related psychological defense mechanisms, be at risk of having poor eating behaviors, and have a display of immature or neurotic defense styles. However, there is limited research that studied the effect of behavioral treatment combined with a structured exercise program, in addressing the issues with neurotic defense styles. The Acceptance and Commitment Therapy (ACT) has shown to be effective in managing body weight issues; however, the effect of including a structured exercise program is not known. This study consists of two phases. Phase one explored the prevalence of being overweight and obese among students from two public universities in Sarawak. Phase two investigated and compared the changes in the Acceptance and Action Questionnaire for Weight (AAQW) score (weight-related psychological flexibility (WRF)), Body Mass Index (BMI), and eating behaviors in overweight and obese university students with immature or neurotic defense styles. The participants were assigned to receive either Acceptance and Commitment Therapy (ACT), Acceptance and Commitment Therapy with structured exercise (ACT-EX), or be placed in a control condition for a six-week, three-arm randomized controlled trial (RCT). The prevalence of being overweight or obese was high. Four out of ten university students were either overweight or obese. The older age group (> 25 years old) and male students were significantly more overweight and obese. The Asian cut-off point for the BMI category was used as a reference. The results from the RCT showed that the ACT-EX was significantly more effective in reducing the AAQW score (improved WRF), BMI, and eating behaviors than the ACT alone. A more mature defense style was displayed among the participants who received the ACT rather than the ACT-EX. Overall, this study adds further support to the effectiveness of ACT interventions in weight management, WRF, and eating behaviors. Individuals who are overweight or obese (OW/OB) tend to employ less adaptive defense styles; however, this can be altered with the ACT intervention. Furthermore, the integration of exercise in ACT-EX makes it more prominent for weight loss and improving WRF and eating behaviors among OW/OB university students. With the evidence from this study, it is worthwhile to recommend psychologists, health professionals, and fitness trainers integrate ACT with structured exercise to achieve the goal of a weight management program that would likely sustain psychological flexibility in terms of weight, eating behaviors, and defense styles.